Phytochemistry and Antidiabetic Evaluation in-vitro and in-vivo of Ethyl Acetate Fractions from Sungkai Leaves (Peronema canescens Jack) - Aini, Qurrota; Latief, Madyawati; Tarigan, Indra Lasmana; MASRURI, Masruri (Chemistry Department, The University of Brawijaya, 2024)
The paper reports the in vivo and in vitro antidiabetic activity of bioactive compounds composed of ethyl acetate fractions from Sungkai (Peronema canescens Jack). The fractions are obtained from vacuum liquid chromatography (F1, F2 and F3). Phytochemicals screening, UV-Vis and FTIR spectrometry analysis is applied to detect secondary metabolite composed of the fractions. In addition, in vitro antidiabetic capability is measured inhibiting a-amylase activity, and in vivo evaluation is conducted using diabetic rat's model induced by alloxan. It was found that fraction collected as a white precipitate. The phytochemical analysis indicated positive for flavonoid. UV-Vis and FTIR spectra support the data. Moreover, capability of the fractions to inhibit a-glucosidase activity in the range 5-100 ppm does not show the activity. Conversely, the in vivo evaluation from fraction 2 at concentration 600 mg/Kg of body weight has antidiabetic in 50.16%. This result comparable to that of glibenclamide as a control. This finding lead to further evaluation for structural elucidation.